KADERISASI KEANGGOTAAN KESATUAN AKSI MAHASISWA MUSLIM INDONESIA (KAMMI) (STUDI KASUS KOMUNIKASI ORGANISASI DI KOMISARIAT AL GHUROBAH UNIVERSITAS TADULAKO) - Mutmainah (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2019)
This study uses a case study research method (case study). This type of research was conducted by means of qualitative descriptive. Data collection techniques were carried out by means of observation and in-depth interviews. The informants in this study amounted to 8 (eight) general chairmen, cadre coordinators and 6 (six) administrators and research sites on Jl. Ongka Malino, East Palu District, South Lolu Village. This study uses interactive data analysis techniques consisting of 3 stages, namely data reduction (Data Reduction), data presentation (Data Display) and verification (Verification). The results of this study indicate that the form of communication at KAMMI Komisariat Al-Ghuroba UNTAD is internal communication consisting of vertical and horizontal communication. For the cadre process, following the flow of the existing cadre at KAMMI, namely following PRA DM1, DM1, MK1, AB1 Supplement, IJDK AB1 Certification, Then after being declared graduated, the cadre will get a new status title, namely AB 1 (Ordinary Member). As for the implementation of cadre at KAMMI, UNTAD Al Ghuroba Commissariat using participatory or participation methods while the alternatives used are information, questions and answers, assignments, discussions, practices and games. As for the coaching, there are several activities, both spiritual and physical. The coaching activities included MK Khos, MK classical, Mahabbah Haraki, Rihlah, Night of Faith and piety (Mabit), Rihlah and KAMMI camp.